2018
DOI: 10.21873/invivo.11302
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Resistance Modifying Activities of Nigella sativa Essential Oil and its Active Compounds Against Listeria monocytogenes

Abstract: Abstract. Background/Aim: N. sativa essential oil (EO) and its compounds (thymoquinone, carvacrol and p-cymene)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…N. sativa showed antibacterial effect against Salmonella , Helicobacter pylori , and Escherichia coli strains (Bakal, Bereswill, & Heimesaat, ). In addition, Listeria monocytogenes proved to be susceptible toward N. sativa EO, Thq, and Car (Mouwakeh, Telbisz, Spengler, Mohácsi‐Farkas, & Kiskó, ). It has been demonstrated that N. sativa EO was effective against Salmonella enterica causing the food‐borne disease salmonellosis (Ashraf et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…N. sativa showed antibacterial effect against Salmonella , Helicobacter pylori , and Escherichia coli strains (Bakal, Bereswill, & Heimesaat, ). In addition, Listeria monocytogenes proved to be susceptible toward N. sativa EO, Thq, and Car (Mouwakeh, Telbisz, Spengler, Mohácsi‐Farkas, & Kiskó, ). It has been demonstrated that N. sativa EO was effective against Salmonella enterica causing the food‐borne disease salmonellosis (Ashraf et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Efflux pumps are transport protein in bacteria associated with elimination of toxic molecules from cell to external environment, moreover, this mechanism play essential role in reducing bacteria killing and develop bacteria resistance. The killing mechanism of Nigella Sativa extract on Serratia marcesence could be involved directly in the effect on cell membrane efflux pumps, which reduce bacteria resist and survive [39,40].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all of the bioactive constituents (p-cy, Thq, Car, Thy) showed a direct antibacterial effect against C. trachomatis D. As only one study related to anti-chlamydial activity of EOs has been published, further studies are needed to clarify the exact mechanisms of their effects. Car and Thq were able to damage the cell membrane of S. aureus and Listeria monocytogenes [14,26]. Thy, which is the most common constituent of EOs obtained from Thymus spp.…”
Section: Discussionmentioning
confidence: 99%
“…N. sativa EO extraction was performed as reported earlier [14]. Thymoquinone (Thq), thymol (Thy), and carvacrol (Car) were purchased from MilliporeSigma ( St. Louis, MO, USA) and p-cymene (p-cy) was purchased from Alfa Aesar (Haverhill, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation